(3fRgI Phi GdCdHGH hJMaI fLHGA GdCfLGHs - (3eMeO Hf CMeO Hf eMeO HfjSjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO ajbhd GdYHO GdabjQ Edi ehdGg eMeO Hf CMeO Hf eMeO HfjS gPg ahGFO EfJNHJgG hfcJ EfJbjJgG dJchf MdjI dTQM GdefjI dfGXegG SjOfG GdEeGe CHj YHO Gddg SjOi eMeO Hf ZGRi hSejJgG fRgI Phi GdCdHGH s
(3BNQgG (B:s
(3hgPG GdMGaX Hf MLQ PcQ ai ChGNQ cJGH GdCOH ef TQM GdUMjM Cf GdEeGe GHG GdYHGS CMeO Hf CHj CMeO GdWHQi GdTGaYi LeY ahGFO GdMOjK GdePchQ hRGO Ydjg HahGFO CNQi aGfXQg JSJaO hHGddg GdJhajb s
(3GdfSNI HgG MhGTs
(3fSNI eYfhfI HGdMHQ GdCMeQ hGdMHQ GdCShO hYdjgG eWGdYI hJUMjMGJ hTQhMs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdQjGVjGJs